Building Positive Classroom Interaction through Positive Discourse - Adriansyah Abu Katili (Jambura Journal of English Teaching and Literature, 2022)
This article discusses how to build positive classroom interaction through positive classroom discourse. This article is focused on lecturers’ utterances that consist of lecturers’ sentence construction and speech acts. The lecturers’ speech acts were discussed based on Sinclair and Coulthard’s theory of classroom speech acts and Austin’s speech acts that were developed by Searle. Both sentence construction and the lecturers’ classroom speech acts affect classroom interaction. Positive discourse builds positive classroom interaction. In terms of sentence construction, the lecturer constructed Designedly Incomplete Utterance (DIU). This was designed to drive the students to complete them. In terms of lecturers’ speech acts, the lecturers performed elicitation and the students responded to it. The lecturer’s negative speech acts were an expressive illocutionary act of anger that built the classroom negatively. The DIU and elicitation were categorized as positive discourse and the anger expression was negative.